Carotid Atherosclerotic Plaque Matrix Metalloproteinase-12–Positive Macrophage Subpopulation Predicts Adverse Outcome After Endarterectomy - Scholtes, Vincent P. W. (Blackwell Publishing Ltd, 2012)
BACKGROUND: Matrix metalloproteinase-12 (MMP-12) promotes atherosclerosis in animal models. MMP-12 is expressed in only a subset of foam-cell macrophages (FCMs) in human plaques. We investigated whether the prevalence of this MMP-12–expressing subpopulation is a prognostic indicator of adverse outcome in patients after carotid endarterectomy (CEA). METHODS AND RESULTS: Serial sections of culprit lesions from 236 patients who underwent CEA and had undergone 3 years of clinical follow-up were stained immunocytochemically for MMP-12 and for CD68, and the MMP-12/CD68 ratio was used to quantify the MMP-12–expressing subpopulation. A high MMP-12/CD68 ratio correlated with a high content of lipid and total macrophages and a low content of vascular smooth muscle cells, as well as with MMP-8 (R=0.211, P=0.001), MMP-9 (R=0.251, P<0.001), and cleaved caspase-3 (R=0.142, P=0.036) activity measured in a neighboring segment. Dual immunohistochemical examination confirmed the location of MMP-12 in a subpopulation of MMP-8– and MMP-9–positive FCMs, whereas all apoptotic FCMs were MMP-12 positive. Patients who yielded plaques within the highest quartile compared with the lowest quartile of MMP-12/CD68 ratio had a 2.4-fold (hazard ratio, 2.4; 95% CI, 1.1- to 5.1-fold; adjusted P=0.027) increased risk of major adverse cardiovascular event and a 3.4-fold (3.4; 1.2- to 9.6-fold, P=0.024) increased risk for stroke. CONCLUSIONS: The prevalence of an MMP-12–positive subset of FCMs is a prognostic marker for adverse clinical outcome after CEA.